Comparison of Periodontal Ligament Stem Cells Isolated from the Periodontium of Healthy Teeth and Periodontitis-Affected Teeth - Sara Soheilifar; Iraj Amiri; Mohsen Bidgoli; Morad Hedayatipanah (Tehran University of Medical Sciences, 2016)
Objectives: Stem cell (SC) therapy is a promising technique for tissue regeneration. This study aimed to compare the viability and proliferation ability of periodontal ligament stem cells (PDLSCs) isolated from the periodontium of healthy and periodontitis-affected teeth to obtain an autologous, easily accessible source of SCs for tissue regeneration in periodontitis patients. Materials and Methods: The PDLSCs were isolated from the roots of clinically healthy premolars extracted for orthodontic purposes and periodontally involved teeth with hopeless prognosis (with and without phase I periodontal treatment). Cells were cultured and viability and proliferation ability of third passage cells in each group were evaluated using the methyl thiazol tetrazolium assay. The results were statistically analyzed using t-test. Results: No SCs could be obtained from periodontitis-affected teeth without phase I periodontal treatment. The viability of cells was 0.86±0.13 OD/540 in healthy group and 0.4±0.25 OD/540 in periodontitis-affected group (P=0.035). The proliferation ability (population doubling time) of cells obtained from healthy teeth was 4.22±1.23 hours. This value was 2.3±0.35 hours for those obtained from periodontitis-affected teeth (P=0.02). Conclusions: Viability and proliferation ability of cells isolated from the periodontium of healthy teeth were significantly greater than those of cells isolated from the periodontitis-affected teeth.